Analysis of Reinforced Concrete Durability Against Corrosion Due to Chloride Penetration - Gabriel Jose Posenti Ghewa (Praxis : Jurnal Sains, Teknologi, Masyarakat dan Jejaring, 2023)
Corrosion in reinforced concrete is a serious problem in the construction industry as it can reduce the strength and service life of concrete. Chloride penetration has been identified as one of the main causes of corrosion in reinforced concrete. Therefore, in this study, an analysis of the resistance of reinforced concrete to corrosion due to chloride penetration was conducted. The testing method included varying the concentration of chloride in seawater and testing the compressive strength of reinforced concrete after exposure to chloride for a certain period of time. The results showed that the higher the concentration of chloride, the faster the corrosion occurred and the lower the compressive strength of reinforced concrete. Therefore, prevention efforts are needed by using additives such as corrosion inhibitors or reducing the chloride content in the concrete mix to increase the resistance of reinforced concrete to corrosion due to chloride penetration. From the test results, the use of 5% silica fume by weight of concrete increased the compressive strength of concrete by 13% and reduced the rate of chloride penetration by 30%, as assessed from the chloride ion penetrability value.